2013
DOI: 10.2196/jmir.2721
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sentiment Analysis for Capturing Patient Experience From Free-Text Comments Posted Online

Abstract: BackgroundThere are large amounts of unstructured, free-text information about quality of health care available on the Internet in blogs, social networks, and on physician rating websites that are not captured in a systematic way. New analytical techniques, such as sentiment analysis, may allow us to understand and use this information more effectively to improve the quality of health care.ObjectiveWe attempted to use machine learning to understand patients’ unstructured comments about their care. We used sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
206
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(225 citation statements)
references
References 22 publications
3
206
0
1
Order By: Relevance
“…For this, they use social networks, like Twitter and Facebook as sources to review written texts in form of comments, which contain opinions about their registered brand. This literature review found different types of works framed within different applications; in tourism [10] [11], movie reviews [12] [13], sports [14] politics [15] [16] education [17], health [18], finance [19], and opinion reviews on automobiles [20].…”
Section: Applicationmentioning
confidence: 99%
“…For this, they use social networks, like Twitter and Facebook as sources to review written texts in form of comments, which contain opinions about their registered brand. This literature review found different types of works framed within different applications; in tourism [10] [11], movie reviews [12] [13], sports [14] politics [15] [16] education [17], health [18], finance [19], and opinion reviews on automobiles [20].…”
Section: Applicationmentioning
confidence: 99%
“…Each thread t steps: (i) QoL dimension identification and (ii) Degree former is intended to identify those threads where at le ns considered in the EuroQol questionnaire (mobility, s /discomfort, anxiety/depression) is addressed. The latte means of sentiment analysis techniques [6], the degree ach of the identified QoL dimensions. These two inf ow to virtually score the corresponding EuroQol questi he conversion to a proper UC using the standard EuroQ gorithm.…”
Section: Collaborative Filtermentioning
confidence: 99%
“…Studies pertaining to the patient view have mostly relied on questionnaire-based surveys that employ structured measurements of patient reported outcomes [10][11][12]. Perhaps, a better way to understand the patient view would be exploring an alternative source of data.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, a better way to understand the patient view would be exploring an alternative source of data. Today, patients have begun to report their healthcare experience on social networks [12]. As these reports come directly from patients with no filtering in between, they have the potential to represent true patient experience.…”
Section: Introductionmentioning
confidence: 99%